ANALISIS HUBUNGAN BEBAN KERJA FISIK, MASA KERJA, USIA, DAN JENIS KELAMIN TERHADAP TINGKAT KELELAHAN KERJA PADA PEKERJA BAGIAN PEMBUATAN KULIT LUMPIA DI KELURAHAN KRANGGAN KECAMATAN SEMARANG TENGAH - Kusgiyanto, Wahyu; Suroto, Suroto; Ekawati, Ekawati (Jurnal Kesehatan Masyarakat (e-Journal), 2017)
Indonesia has determined that the maximum length of working time is 8 hours and need take a rest for workers. Prolonged working time more than that can decrease of work efficiency, increase fatigue, accidents and occupational diseases. In the home industry of making lumpia’s wrappers have risk factor for the occurrence of occupational fatigue where the workload in the informal industry determined from the workers themselves. The purpose of this research was to analyze the correlation between physical workload, work periods, age and gender with the level of occupational fatigue. This was quantitative research with analytic survey using cross sectional design. The dependent variable of this research was occupational fatigue and independent variables were physical workload, work periods, age and gender. Population of this research were workers part of making lumpia’s wrappers with the total of 31 people and sampling method was using total sampling. Data of occupational fatigue collected using reaction timer measurement, work pulse measurement using pulsemeter and other data based on interview of respondent data sheet. Data analyzed using Pearson Product Moment correlation test for normal data and Rank Spearman for abnormal data with α = 0,05. Statistical results test showed that there were correlation between physical workload (sig = 0,002) and age (sig = 0,008) and there were no correlation between work periods (sig = 0,967) and gender (sig = 0.233) with the level of occupational fatigue.